2020
DOI: 10.21203/rs.3.rs-114088/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence of Helicobacter Pylori Infection and Associated Factors Among Gastritis Patents in Yekatit 12 Teaching Hospital Addis Ababa Ethiopia

Abstract: Introduction: Helicobacter pylori colonize the stomach of about ~50% of the world’s human population and infection is more in clients with dyspeptic conditions and its associated with the severity of gastritis. The present study revealed that the magnitude of H. Pylori and burden of the bacterial infection as well as the contribution of H. Pylori for gastritis and also assesses the current prevalence of H. Pylori infection.Objective: To evaluate the prevalence of Helicobacter Pylori infection and associated fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
2
2
Order By: Relevance
“…It was lower Canadian Journal of Infectious Diseases and Medical Microbiology than studies conducted in Sudan (70%) [26], Sekota (northeast Ethiopia) (64.8%) [52], and Pakistan (66.66%) [53]. In contrast, the fndings of the current study were higher than reports from Debre Tabor (Ethiopia) (34%) [18], Addis Ababa Ethiopia (25.9%) [12], Nepal (17%) [54], Ghana (14.2%) [55], United Arab Emirates (41%) [56], and Iceland (3.4%) [57]. Te diferences in fndings among various studies can be explained by variations in sociodemographic, socioeconomic, behavioral, types of diagnostic kits having diferent sensitivities, and environmental factors, as well as variations in the number of study population.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…It was lower Canadian Journal of Infectious Diseases and Medical Microbiology than studies conducted in Sudan (70%) [26], Sekota (northeast Ethiopia) (64.8%) [52], and Pakistan (66.66%) [53]. In contrast, the fndings of the current study were higher than reports from Debre Tabor (Ethiopia) (34%) [18], Addis Ababa Ethiopia (25.9%) [12], Nepal (17%) [54], Ghana (14.2%) [55], United Arab Emirates (41%) [56], and Iceland (3.4%) [57]. Te diferences in fndings among various studies can be explained by variations in sociodemographic, socioeconomic, behavioral, types of diagnostic kits having diferent sensitivities, and environmental factors, as well as variations in the number of study population.…”
Section: Discussioncontrasting
confidence: 82%
“…Rural residents had 5.55 times higher odds of H. pylori infection than their counterparts in urban areas. A similar study, which was conducted in Assosa (Ethiopia) [58], Alaska, U.S.A. [46], Addis Ababa (Ethiopia) [12], and Pakistan [59], identifed this variable to be signifcantly associated with H. pylori infection. However, studies conducted in Dessie (Ethiopia) [16], Iraq [50], and Egypt [60] showed that residence was not signifcantly associated with H. pylori infection.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…from the hands of the father of Repent was not an independent determinant of H. pylori infection in the patients. However, a previous study from a closer analogy revealed that mouth-to-mouth kissing was an independent predictor of H. pylori infection in patients, 42 as the difference might be due to the smaller sample size of Orthodox Tewahido Christians in the present study. In addition, our study findings disagree with the previous study report from islands of Indonesia, which showed that ethnicity is an independent risk factor for H. pylori infection.…”
Section: Dovepresscontrasting
confidence: 64%